High urinary albumin/creatinine ratio at admission predicts poor functional outcome in patients with acute ischaemic stroke. Issue 3 (March 2017) - Watanabe, Yoko; Suda, Satoshi; Kanamaru, Takuya; Katsumata, Toshiya; Okubo, Seiji; Kaneko, Tomohiro; Mii, Akiko; Sakai, Yukinao; Katayama, Yasuo; Kimura, Kazumi; Tsuruoka, Shuichi
Abstract: Aim: Albuminuria and a low estimated glomerular filtration rate (eGFR) are widely recognized indices of kidney dysfunction and have been linked to cardiovascular events, including stroke. We evaluated albuminuria, measured using the urinary albumin/creatinine ratio (UACR), and the eGFR in the acute phase of ischaemic stroke, and investigated the clinical characteristics of ischaemic stroke patients with and those without kidney dysfunction. Methods: The study included 422 consecutive patients admitted between June 2010 and May 2012. General blood and urine examinations were performed at admission. Kidney dysfunction was defined as a low eGFR (<60 mL/min per 1.73 m 2 ), high albuminuria (≥30 mg/g creatinine), or both. Neurological severity was evaluated using the National Institutes of Health Stroke Scale (NIHSS) at admission and the modified Rankin scale (mRS) at discharge. A poor outcome was defined as a mRS score of 3–5 or death. The impacts of the eGFR and UACR on outcomes at discharge were evaluated using multiple logistic regression analysis. Results: Kidney dysfunction was diagnosed in 278 of the 422 patients (65.9%). The eGFR was significantly lower and UACR was significantly higher in patients with a poor outcome than in those with a good outcome. In multivariate analyses performed after adjusting for confounding factors, UACR >31.2 mg/g creatinine (OR, 2.58; 95% CI, 1.52–4.43; P = 0.0005) was independently associated with a poor outcome, while a low eGFR was not associated. Conclusions: A high UACR at admission may predict a poor outcome at discharge in patients with acute ischaemic stroke. Summary at a Glance: This study showed how high UACR but not eGFR measured at the time of acute ischemic stroke predicts poor functional outcome.